Abu Sayyaf Group di Filipina Selatan setelah Bangsamoro Autonomous Region in Muslim Mindanao - Prakoso Permono (Global Strategis, 2019)
Filipina awal tahun 2019 diwarnai referendum di Filipina Selatan yang mengantarkan pada dibentuknya Bangsamoro Autonomous Region in Muslim Mindanao (BARMM). Konflik, instabilitas kawasan, dan perkembangan ancaman terorisme di Filipina Selatan khususnya dan umumnya di seluruh Filipina diharapkan berakhir dengan sebuah konsensus damai dan demokratis seiring terbentuknya pemerintahan transisi di BARMM. Harapan terciptanya perdamaian dengan keberadaan BARMM dalam tulisan ini dikaji secara spesifik dari salah satu kelompok teror yang berkembang di kawasan Filipina Selatan, Abu Sayyaf Group (ASG). Keberadaan ASG pada mulanya merupakan dampak kekecewaan usaha perjanjian damai yang diinisiasi pemerintah dan kelompok teror terbesar saat itu Moro National Liberation Front (MNLF), seiring dengan perkembangan waktu kelompok ASG bertransformasi menjadi sebuah kelompok kriminal dengan modus operandi penculikan dan permintaan tebusan, sekalipun tidak sepenuhnya meninggalkan posisi awalnya sebagai kelompok teror dengan kehendak separatis ideologis. Penelitian ini berusaha menjawab potensi dampak yang muncul pada ASG dengan dibentuknya BARMM di kawasan Filipina Selatan. Sayangnya opsi-opsi melemah dan bubarnya ASG yang disebabkan oleh keberadaan BARMM hanya dapat terjadi bila tercipta good governance dan penyelesaian persoalan dasar seperti kemiskinan dan potensi radikalisasi yang terus berkembang. Jawaban dari masa depan ancaman teror ASG di Filipina Selatan akhirnya tergantung seberapa besar penguasaan wilayah, penegakan hukum, dan pengentasan kemiskinan di Filipina Selatan.  Kata-kata kunci: Abu Sayyaf Group, Filipina Selatan, Bangsamoro Autonomous Region in Muslim Mindanao. Early 2019 in the Philippines was marked by a referendum in Southern Philippines which led to establishment of Bangsamoro Autonomous Region in Muslim Mindanao (BARMM). Conflict, regional instability, and terrorism threats development especially in Southern Philippines and generally in all over Philippines are expected to end with a peaceful and democratic consensus as transitional government has formed already in the BARMM. The hope of creating peace with the presence of BARMM in this paper is specifically examined from one of terror group in the Southern Philippines region, the Abu Sayyaf Group (ASG). The existence of the ASG was initially a result of disappointment caused by peace agreement efforts initiated by Moro National Liberation Front (MNLF) the largest terror group at that time, along with its development the ASG Group transforming into a criminal group with kidnapping and ransom as their main modus operandi, but not completely abandoned its initial position as a ideological terror group with separatism agenda. This research seeks to address the potential impacts of BARMM establishment in the Southern Philippines region to the development of ASG Group. Unfortunately, the options to weaken and to liquidate ASG caused by the presence of BARMM can only occur if good governance is created and the basic problems such as poverty in the region are resolved. The answer to the future of ASG terror threat in the Southern Philippines ultimately depends on how much territorial control, law enforcement, and poverty alleviation process in the Southern Philippines. Keywords: Abu Sayyaf Group, Southern Philippines, Bangsamoro Autonomous Region in Muslim Mindanao.